Current airway management practices after a failed intubation attempt in Australian and New Zealand emergency departments. (5th February 2021) - Arnold, Isaac; Alkhouri, Hatem; Badge, Helen; Fogg, Toby; McCarthy, Sally; Vassiliadis, John
Abstract: Objective: The aims of the present study were to describe current airway management practices after a failed intubation attempt in Australian and New Zealand EDs and to explore factors associated with second attempt success. Methods: Data were collected from a multicentre airway registry (The Australian and New Zealand Emergency Department Airway Registry). All intubation episodes that required a second attempt between March 2010 and November 2015 were analysed. Analysis for association with success at the second attempt was undertaken for patient factors including predicted difficulty of laryngoscopy, as well as for changes in laryngoscope type, adjunct devices, intubator and intubating manoeuvres. Results: Of the 762 patients with a failed first intubation attempt, 603 (79.1%) were intubated successfully at the second attempt. The majority of second attempts were undertaken by emergency consultants (36.8%) and emergency registrars (34.2%). A change in intubator occurred in 56.5% of intubation episodes and was associated with higher second attempt success (unadjusted odds ratio [OR] 1.85; 95% confidence interval [CI] 1.29–2.65). In 69.7% of second attempts at intubation, there was no change in laryngoscope type. Changes in laryngoscope type, adjunct devices and intubation manoeuvres were not significantly associated with success at the second attempt. In adjusted analyses, second attempt success was higher for a change from a non‐consultant intubator to a consultant intubator from any specialty (adjusted OR 2.31; 95% CI 1.35–3.95) and where laryngoscopy was not predicted to be difficult (adjusted OR 2.58; 95% CI 1.58–4.21). Conclusions: The majority of second intubation attempts were undertaken by emergency consultants and registrars. A change from a non‐consultant intubator to a consultant intubator of any specialty for the second attempt and intubation episodes where laryngoscopy was predicted to be non‐difficult were associated with a higher success rate at intubation. Participation in routine collection and monitoring of airway management practices via a Registry may enable the introduction of appropriate improvements in airway procedures and reduce complication rates. Abstract : First descriptive study of airway management manoeuvres following a failed intubation attempt in Australian and New Zealand EDs. A change in intubator occurred in just over half of intubation episodes. A predicted non‐difficult airway, any change in intubator and a change from a non‐consultant to consultant intubator were associated with higher success at second intubation attempt while changes in intubation devices and other manoeuvres did not improve success at the second attempt.